The Effectiveness of Chest Physiotherapy Education in Handling Acute Respiratory Infections in Toddlers on Mother's Knowledge - Haswita, Haswita; Arthamevia Putri, Tasya; Yulia Purwaningtyas, Rizki; Waspada, Edy (Chakra Brahmanda Lentera Institute, 2024)
Background: Acute respiratory tract infection is one of the respiratory disorders that children in Indonesia often suffer. Acute respiratory tract infection is the infection that most often causes death and disease worldwide. This study aims to determine the effectiveness of health education about chest physiotherapy in the treatment of acute respiratory tract infections in toddlers on the level of maternal knowledge at Early Childhood Education Darusallam Kalibaru. Methods: This quantitative study uses a pre-experimental approach with a one-group pre-post test design. The sampling technique employed is total sampling, with a sample size of 50 respondents. The instrument used for data collection is a questionnaire, and the data analysis is performed using the Wilcoxon signed-rank test. Results: The results showed that maternal knowledge was less than 30 (60%) after being given health education. The level of maternal knowledge was good at 31 (62%). The Wilcoxon test obtained a p-value of 0.000<0.05, so there was a significant influence on the level of maternal knowledge before and after the provision of safety education. Conclusion: This study is expected to be informative for mothers as one of the techniques for handling acute respiratory tract infections in toddlers. Future research should assess the long-term impact of health education on chest physiotherapy in managing acute respiratory infections in toddlers.